Navigating the SWIG spaces / Trikartinangsih Byas - Byas, Trikartinangsih (Faculty of Architecture, Planning and Surveying, 2013)
Investigation approach to migrants adaptation process in host countries has always been place specific, in order to understands the whole connections to all aspect of life.